Physicochemical characterization of cereals grains and functionality of amaranth (Amaranthus caudatus) and quinoa (Chenopodium quinoa) flours - Urbina Dicao, Karen Solange; Santacruz Terán, Stalin Gustavo; Guapi Álava, Gina Mariuxi; Revilla Escobar, Karol; Aldas Morejon, Jhonnatan Placido (Revista Colombiana de Investigaciones Agroindustriales, 2023)
Abstracto Amaranth and quinoa, like other cereals, can be used to obtain products with high nutritional value. Currently, they are considered basic foods in the family basket of the inhabitants of the Andean zones, which has led to the need to promote the sustainable development of their crops. Therefore, the main objective of this study was to evaluate the physicochemical characteristics of cereals and the functionality of amaranth and quinoa flours. For this purpose, a completely randomized, one-factor statistical model was applied, consisting of three replicates. It was determined that amaranth had a higher content of protein (12,41 %), fat (6,74 %), total carbohydrates (67,09 %) and seed index (5,37 mg), compared to quinoa, which had a higher capacity for hydration (0,55 g/seed) and swelling (0,56 ml/seed) of the seeds. Regarding the functional properties, the type of cereal did not influence the characteristics of the flours, because there was no significant difference (p < 0,05), however, it was demonstrated that amaranth flour had a better absorption capacity (137,60 ml/100 g) and retention (83,60 ml/100 g) in water, while quinoa flour had a higher absorption capacity (96,03 ml/100g) and retention (90,50 ml/100 g) in oil, 60 ml/100 g) in water, while quinoa flour had a higher absorption capacity (96,03 ml/100 g) and retention (90,50 ml/100 g) in oil, on the other hand, amaranth flour obtained a higher emulsifying activity (3,00 %) and stability (5,67 %), foaming capacity (2,52 %) and stability (2,62 %). Therefore, it is concluded that the cereals studied can be used to obtain flour and products derived from them